2016
DOI: 10.1159/000438629
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-TAZ Administration Alleviates Osteoporotic Phenotypes in the Femoral Neck of Ovariectomized Rats

Abstract: Background: Osteoporosis is characterized by impairment of bone mass, strength, and microarchitecture, leading to the susceptibility to fragility fractures, especially in femoral neck region. Transcriptional coactivator with PDZ-binding motif (TAZ) facilitates osteogenesis while suppressing adipogenesis via regulation of transcriptional activities of runt-related transcription factor 2 and peroxisome proliferator-activated receptor γ. Here, we validated the role of TAZ in vivo using an ovariectomized (OVX) rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Except for TAZ expression, the upregulation of RUNX2 and OCN expression in the IRS-1 overexpression group also suggested that IRS-1 could enhance the RUNX2- and OCN-driven osteogenic gene expression accordingly. At first, we discovered that IRS-1 and RUNX2 mRNA levels were increased at the early stage of osteogenesis, while the OCN mRNA levels presented a delayed increase, as shown in previous studies (Born et al, 2012; Zhang et al, 2016). In addition, the mRNA and protein levels of RUNX2 and OCN were both significantly increased after 3 days' induction of the osteogenic medium in the IRS-1 overexpression group.…”
Section: Discussionsupporting
confidence: 80%
“…Except for TAZ expression, the upregulation of RUNX2 and OCN expression in the IRS-1 overexpression group also suggested that IRS-1 could enhance the RUNX2- and OCN-driven osteogenic gene expression accordingly. At first, we discovered that IRS-1 and RUNX2 mRNA levels were increased at the early stage of osteogenesis, while the OCN mRNA levels presented a delayed increase, as shown in previous studies (Born et al, 2012; Zhang et al, 2016). In addition, the mRNA and protein levels of RUNX2 and OCN were both significantly increased after 3 days' induction of the osteogenic medium in the IRS-1 overexpression group.…”
Section: Discussionsupporting
confidence: 80%
“…ALP play an important role in the process of bone calcification; it will increase when calcification is abnormal [64]. High serum ALP level may interfere with calcium absorption [65,66,67,68]. The results illustrated that the high dose of CPPH-Ca treatment could restore calcification to a normal level, and that calcium in HCPPH-Ca was more easily absorbed, calcified and its effect was better compared with inorganic calcium, even in the HGCa.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our results illustrated that HCPPH-Ca treatment could effectively improve bone index parameters, and more effective absorption and utilization of calcium were found in rats fed HCPPH-Ca compared with inorganic calcium and even HGCa [67]. BMD and BMC are the gold standards for the evaluation of low-calcium deficiency risk [66]. In addition, the BMD of femur and tibia were markedly reduced in the model and HCaCO 3 groups compared with the HCPs-Ca, HGCa and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Given the critical roles of TAZ underlying osteogenic differentiation of MSCs from diverse sources, it is of great interest and importance to translate these findings into therapies for bone repair and regeneration. Local delivery of TAZ by lentivirus alleviated the osteoporotic phenotypes in the femoral neck of ovariectomized rats [ 42 ]. Several research groups have successfully identified several chemical or bioactive compounds such as TM-25659, epicatechin gallate, Phorbaketal A, IBS008738, kaempferol, and ethacridine as TAZ activators that generated the corresponding biological effects mediated by TAZ in diverse cell types [ 23 , 24 , 26 , 40 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%